Sex, Race and Gender: Contemporary Women Artists of Color, the Case of Kara Walker - Dekel, Tal (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
This paper deals with the ways women of color in the visual arts express their perceptions of their own sexuality, with the work of Kara Walker as the centerpiece. The work reviews early conceptions of female sexuality, drawing on the history of colonialism and slavery, using tools from various discourses and disciplines including post-colonialism, politics of identities, politics of differences and feminism.